The AI Co-Founder: Fostering Entrepreneurial and Design-Thinking Mindsets in Engineering and Management Education - Dubey, Archi; Baghel, Dipti; Kalita, Rijumani; Sharma, Menka; Lashkari, Sunaina (Journal of Engineering Education Transformations, 2026)
This paper addresses the failure of traditional engineering and management education to impart the real-world entrepreneurship and design thinking skills required by the Fourth Industrial Revolution. Its core contribution is the introduction of the AI-Augmented Venture Ideation (AAVI) model, a novel pedagogical framework that integrates specific AI tools across the entire venture creation lifecycle-from problem discovery to market validation. The paper details how this model transforms AI from a simple tool into a sophisticated teaching partner, shifting the focus of skill development from rote execution to higher-level strategic direction and critical evaluation. While also discussing the inherent risks of algorithmic bias and skill atrophy, the work concludes that a structured approach like the AAVI model is essential for fundamentally reshaping entrepreneurship education for a future built on human-AI collaboration.